Amine-functionalized mesoporous silica coated ceramics for formaldehyde adsorption - Afrin, Nahid Sajia; Bora, Tanujjal; Supamas Danwittayakul; Ekbordin Winijkul; Bhawat Traipattanakul; His Majesty the King's Scholarships (Thailand) (Pathum Thani : Asian Institute of Technology, 2021)
Formaldehyde is one of the highly toxic indoor air pollutants emitted from the building materials, furniture coating and food preservatives, and its removal is therefore important to ensure a safe environment for us. The current study is focused on the synthesis of amine functionalized mesoporous silica coated ceramic sorbent materials to adsorb formaldehyde. The amine functionalized mesoporous silica nanoparticles was synthesized by so-gel technique from tetraethyl orthosilicate (TEOS) as silica precursor and cetyltrimethylammonium bromide (CTAB) as template. The composition of the precursor solution was modified by varying the molar ration of H2O/TEOS and TEOS/APTES. The ceramic substrate was prepared in light casting process from micro sized alumina particles and coated with the amine functionalized silica nanoparticles in dip coating technique. Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersion X-ray Spectroscopy (EDX), Fourier transform infrared (FT-IR) spectroscopy, and N2 adsorption{u2013}desorption isotherms were used to characterize the amine functionalized mesoporous silica nanoparticles, ceramic substrate, and the functionalized mesoporous silica coated ceramic sorbent. The adsorption efficiency of the fabricated sorbent materials was evaluated by desiccator method and the equilibrium characteristics were evaluated by using Langmuir adsorption isotherm. The sample synthesized with H2O/TEOS = 45.5 and TEOS/APTES = 80/20 showed highest adsorption capacity because of its specific surface area, pore diameter and amine groups.
Thesis (M. Sc.) - Asian Institute of Technology, 2021
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Nanotechnology
Keywords: Formaldehyde -- Toxicology; Protective coatings -- Materials; Nanoparticles; Ceramic coating